Viabilidade polínica, genotoxicidade, efeito antiproliferativo e compostos fenólicos de Peltodon longipes Kunth ex Benth. (Lamiaceae) - Kuhn, Andrielle Wouters (2015)
Brazil has got a great economic potential with regard to native medicinal species. The conservation of the plant genetic diversity available is, therefore, of paramount importance. However, the greater part of these species has not been sufficiently studied, mainly in terms of their cytotoxic and mutagenic potential. Among the Brazilian native medicinal plants that have been little studied is Peltodon longipes Kunth ex Benth. a plant popularly known in Brazil as hortelã-do-campo , which is used as stimulant, emmenagogue, antiseptic and anti-inflammatory. To encourage the use of native medicinal resources of a country are necessary studies of characterization of germplasm of species and also provide that they are included in a breeding program, while optimizing the use in folk medicine through cytotoxicity and genotoxicity studies. Thus, the purpose of this study was to estimate the pollen viability of P. longipes, to evaluate the genotoxicity of the aqueous extracts of this species as well to determine phenolic compounds these extracts using chromatographic analysis. The pollen viability of 15 P. longipes accessions collected in 5 municipalities in the state of Rio Grande do Sul, Brazil, was evaluated by using 3 staining methods: 2% acetic orcein, 2% acetic carmine, and Alexander s stain. The genotoxicity of the aqueous extracts of two accessions, i.e., one collected in Santa Maria and the other one in Tupanciretã, was determined by the Allium cepa L. test, whereas the analysis of the phenolic compounds was carried out by high-performance liquid chromatography. Of the 15 accessions of P. longipes, 13 showed high pollen viability, with values above 75% and the methods using 2% acetic carmine and Alexander reactive were more efficient for technical in species. All extracts presented antiproliferative potential, even though this effect was significantly higher in the extracts of the accession collected in Tupanciretã. This accession also showed a higher amount of rosmarinic acid and kaempferol, which may be linked to the effects observed in these extracts. Only the extracts of the accession collected in Santa Maria showed genotoxic potential.